Fourth industrial revolution in developing countries: a case on Bangladesh - Islam, Md Asadul; Jantan, Amer Hamzah; Hashim, Haslinda; Choo, Wei Chong; Abdullah, Mirza Manirajah; Rahman, Md Adnan; Abdul Hamid, Abu Bakar (Allied Academies, 2018)
This study particularly focuses on Industry 4.0 in developing countries and, in particular, that of Bangladesh, which has been recognised as one of the fastest growing economies in South Asia. Prior to collecting the required data, a review was carried out on Industry 4.0 and the current prospect of it in the developing countries. The field study consisted of ten semi-structured interviews comprising of ten main questions concerning Industry 4.0 with ten scholars from both the Bangladeshi universities and various worldwide corporate sectors. The interviews lasted approximately thirty minutes and were conducted in English. After a successful analysis of all the interview transcripts, the study finds five main challenges along with some opportunities to apply Industry 4.0 in Bangladesh. The challenges include poor infrastructure, availability of cheaper labour, and expensive installation of technologies, lack of government supports and lack of knowledge. With this being the first research project regarding Industry 4.0 in Bangladesh, the findings of the study generate some recommendations that could be effective for the decision makers both in government and the private sector.